270 ENHANCING CAPACITY TO CONSENT IN AN OLDER PERSON RESIDENTIAL CARE FACILITY; USING SPEECH AND LANGUAGE THERAPY TO MAXIMISE COMMUNICATION. (25th October 2022) - Hogan, FH; Ahern, A; Byrne, MF
Abstract: Background: For consent to be valid the resident must be able understand the information and communicate their choice. People with dementia can have a number of communication deficits; difficulty word finding, tendency to digress and repeat themselves, understanding the spoken word, maintaining a conversation topic without losing track, using semantically empty words (e.g. 'thing', 'stuff') in place of content words. This can limit their ability to express wishes and preferences. Out of 100 residents in our Older Person Residential Care facility 48% require some supports with communication; 25 diagnosed with dementia, 8 suspected (33%) and 15 with cognitive impairment. As per the HSE National Consent policy 2022 we have a duty to maximise capacity for our residents to consent to treatment and interventions. Insight into the factors involved in the communication process between nursing staff and people with dementia is limited. Speech and Language Therapists (SALT) identify the specific nature of communication deficits for a person with dementia. Methods: Our SALT reviewed our residents and advised on actions required to reduce the impact of communication deficits. We implemented a Communication care plan for our residents to include all identified communication abilities and disabilities for both speech and language across all modalities (reading, writing, gesture, symbols). To evidence understanding of consent, all staff interacting with residents were requested to undertake the HSELand National Consent policy module. All staff attended training which involved enhancing communication abilities. Results: In February 2022, 95% of care plans audited had actions to address communication deficits in place. Ad hoc discussion with staff evidenced improved understanding of each resident's communication deficits and necessity to use SALT reviews to enhance capacity to consent. Conclusion: We have demonstrated that the use of SALT to enhance ability to communicate has enhanced capacity to consent for our residents. Staff also demonstrated improved communication practices.